1995
DOI: 10.1088/0957-0233/6/7/004
|View full text |Cite
|
Sign up to set email alerts
|

A novel technique for measuring the thermal conductivity of metallic materials during melting and solidification

Abstract: A new technique for measuring the thermal conductivity of metallic materials during liquidsolid phase transformation is proposed and applied to the determination of the thermal diffusivity and thermal conductivity of Wood's metal (Bi, 48%; Pb, 26%; Cd, 13%; Sn, 13%) at the melting point. The technique incorporates measurements in two sequences: (1) during a one-dimensional propagation of the phase transition interface, and (2) during a quasi-equilibrium state where the interface is stationaly. The position of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…This increase is attributed to the reduction in thermal conductivity the alloy undergoes as it passes from solid to liquid state. Studies of related alloy compositions have shown that the ratio of thermal conductivity in solid and liquid state may be as large as 1.5 (Lamvik and Zhou, 1995). It is apparent in Figure 7 that the bar corresponding to the thermal resistance at 518C and 200 kPa does not follow the indicated trend.…”
Section: Resultsmentioning
confidence: 94%
“…This increase is attributed to the reduction in thermal conductivity the alloy undergoes as it passes from solid to liquid state. Studies of related alloy compositions have shown that the ratio of thermal conductivity in solid and liquid state may be as large as 1.5 (Lamvik and Zhou, 1995). It is apparent in Figure 7 that the bar corresponding to the thermal resistance at 518C and 200 kPa does not follow the indicated trend.…”
Section: Resultsmentioning
confidence: 94%
“…The basic data on Wood's alloy is only sketchy [14,15], but we have concluded against it given the likelihood of high thermal conductivity and extremely large viscosity in the melt and a small thermal gradient across the specimen height. The data of Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Thermophysical property data of Wood's alloy are scarce and sketchy at present in that their temperature dependences are unknown. This state of affair applies to: thermal conductivity at the melting point [12], solid versus liquid mass density, heat capacity, and latent heat of melting [13]; and surface tension, kinematic viscosity, and mass density [14]. The absence of more detailed property data makes it difficult to test the applicability of instability theory.…”
Section: Discussionmentioning
confidence: 99%